In vitro lipolysis and lymphatic absorption of n-3 long-chain PUFA in the rat: influence of the molecular lipid species as carrier. Issue 6 (28th September 2019) - Sehl, Anthony; Couëdelo, Leslie; Chamekh-Coelho, Ikram; Vaysse, Carole; Cansell, Maud
Abstract: The aim of this work was to study the bioavailability of fatty acids (FA), focusing on n -3 long-chain (LC) PUFA, carried by different molecular lipid species, that is, phospholipids (PL) or TAG, with three formulations based on fish oils or marine PL, providing a similar n -3 LC PUFA amount. The digestive lipolysis was first assessed using an in vitro enzymatic model. Then, intestinal absorption and enterocyte metabolism were investigated in vivo, on male Wistar rats through lymph lipid analysis. The in vitro results showed that the release of n -3 LC PUFA from lipolysis was increased by 48 % when FA were provided as PL rather than TAG. The in vivo results demonstrated that EPA and DHA from both TAG and PL were similarly absorbed and incorporated into lymph lipids. However, DHA was mainly distributed at the sn -1/3 positions of lymph TAG when provided as marine PL, whereas it was equally distributed at the three positions with marine TAG. On the whole, even if the molecular lipid species of n -3 LC PUFA did not greatly modify the in vivo digestion and absorption steps, it modulated the rearrangement of DHA on the glyceride positions of the lymph TAG, which may further impact the DHA metabolic fate and tissue accretion. Consequently, the present study has provided data which may be used to formulate lipid diets rich in DHA in the context of an insufficient consumption of n -3 PUFA in Western countries.